Seismic Active Earth Pressure of Limited Backfill with Curved Slip Surface Considering Intermediate Principal Stress - Hui Liu; Dezhi Kong; Wensong Gan; Bingjie Wang (Applied Sciences, 2021)
The traditional method for seismic earth pressure calculation has certain limitations for retaining structures under complex conditions. For example, when the soil width is small, the results obtained by the traditional method will be much larger. Therefore, this paper assumes that the soil slip surface is a logarithmic spiral. Based on the plane strain unified strength theory formula, while also considering the soil arching effects and tension cracks, the analytical solutions of the lateral earth pressure coefficient and the active earth pressure under the earthquake action were deduced. The mechanism and distribution of seismic active earth pressure with limited width were discussed in terms of some relevant parameters. The results indicated that the seismic active earth pressure presented a “convex” nonlinear distribution along the retaining structure. As the contribution of the intermediate principal stress increased, the strength limit of the material was effectively utilized, and the earth pressure was reduced by 22.96%. The resultant force increased as the horizontal seismic coefficient increased. However, this effect was no longer evident when the wall–soil friction angle was close to the internal friction angle. The resultant force action point increased with the wall–soil friction angle, and it should be noted that <semantics>ha>H/3</semantics> was true when <semantics>δ/φ0>0.55</semantics>. Finally, by drawing a comparison with previous studies, we verified that the method proposed in this paper is reasonable and can provide a new idea for subsequent 3D seismic earth pressure research.